Standardization of the model of experimental infection in cattle with anaplasma centrale for the production of immunogens - Lozina, Laura Analía (2018)
Fil: Lozina, Laura Analía. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias. Departamento de Clínicas; Argentina.